2002
DOI: 10.1136/vr.150.12.365
|View full text |Cite
|
Sign up to set email alerts
|

Studies of embryo transfer from cattle clinically affected by bovine spongiform encephalopathy (BSE)

Abstract: Semen from 13 bulls, eight with clinical bovine spongiform encephalopathy (BSE), was used to artificially inseminate (AI) 167 cows with clinical BSE, and their resultant embryos were collected non-surgically seven days after AI. The viable and non-viable embryos with intact zonae pellucidae were washed 10 times (as recommended by the International Embryo Transfer Society) then frozen. Later, 587 of the viable embryos were transferred singly into 347 recipient heifers imported from New Zealand, and 266 live off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In BSE of cattle all the evidence indicates that under natural conditions the BSE agent does not spread horizontally into the environment by any secreta or excreta or vertically through maternal transmission; in other words for BSE cattle are a dead-end host [12,78]. The cycle of infection that caused the BSE epidemic has been established through human intervention by the rendering of BSE-infected carcasses and feeding the produced meat and bone meal to cattle.…”
Section: Shedding Of the Infectious Agentmentioning
confidence: 99%
“…In BSE of cattle all the evidence indicates that under natural conditions the BSE agent does not spread horizontally into the environment by any secreta or excreta or vertically through maternal transmission; in other words for BSE cattle are a dead-end host [12,78]. The cycle of infection that caused the BSE epidemic has been established through human intervention by the rendering of BSE-infected carcasses and feeding the produced meat and bone meal to cattle.…”
Section: Shedding Of the Infectious Agentmentioning
confidence: 99%
“…Until today, no evidence of BSE infectivity in semen, embryos, placenta or milk (Bradley and Wilesmith, 1993;Buschmann and Groschup, 2005;Taylor et al, 1995;Wrathall et al, 2002) have been determined although increased risk of BSE development has been reported for the offspring of infected cows. The practice of feeding cattle with meat and bone meal (MBM) contaminated with infectious prions was proposed as the most likely responsible for the BSE epidemic and some hypotheses on the origin of BSE were considered: (i) the primary existence of sporadic or genetic BSE in cattle before its transmission via MBM Capobianco et al, 2007;Nicholson et al, 2008;Richt and Hall, 2008;Torres et al, 2013); (ii) sheep or goat-scrapie transmission to cattle through MBM (Hill et al, 1998); and (iii) human CJD (Colchester and Colchester, 2005).…”
Section: Bovine Spongiform Encephalopathy (Bse)mentioning
confidence: 94%
“…[104][105][106][107][108][109] Transmission via embryo transfer has also been investigated, but neither infected donor bulls nor infected donor cows were capable of transmitting BSE to recipient heifers or to the offspring. 110 Environmental contamination is not an important source of infection, nor is transmission by birds, ro-dents, or other vectors. 111,112 An epidemiologic review of the BSE prion-infected cattle born after the strict feed ban rules implemented in 1996 revealed that these cases did not have an increased likelihood of originating from UK herds with a high incidence of BSE in the past.…”
Section: Transmission Of Bse Among Cattlementioning
confidence: 99%